Design, fabrication, investigation and analysis of a novel flat evaporator loop heat pipe for cooling high heat flux server chips. (25th January 2022) - Xiong, Kangning; Meng, Like; Wang, Shuangfeng
Highlights: A novel LHP with a flat evaporator has been proposed and tested. SEM, porosity, and capillary rise of different sintered powder size are measured. The heat transfer performance of the novel LHP is studied at heat loads from 50 to 750 W. The performance comparison of the novel LHP is presented. Abstract: A novel loop heat pipe (LHP) with a flat evaporator has been proposed to meet the heat dissipation requirement of high heat flux server CPU. The sintered porous copper wick was provided with a double arrayed vapor channels to increase the evaporation area. And a 1 mm thick smaller particle size copper powder embedded with two 0.5 mm thick stainless steel rings was sintered on the inner surface of the compensation chamber to enhance the strength, and increase the working fluid into the porous wick such that the liquid saturation was enhanced and the dry zone was reduced at high heat flux. Additionally, a dual layer structure condenser was presented to increase the cooling area of the condenser. In this study, the systematic experimental studies were carried out mainly focusing on the optimization of powder size, heat transfer performance of the novel LHP and performance comparison of the novel LHP. The results demonstrated that the sintered copper powder of the 106–150 μm particle size shown the best capillary performance in comparison with other powder sizes. More importantly, in the heat load range of 500–750 W, the novel LHP of filling ratio of 46.1% exhibited better operating thermal characteristics. The minimum values of the LHP thermal resistance and the total system thermal resistance at the heat load of 750 W were 0.040 °C/W and 0.090 °C/W, respectively. Compared with the conventional LHP and the simple water block, the novel flat evaporator LHP was a more promising option when the heat load was higher than 250 W.